Prurigo Pigmentosa: Review of the Literature, Impact of Ketogenic Diets and Proposal of a Hypothesis - Deniz Demircioğlu; Emel Öztürk Durmaz; Cüyan Demirkesen; Sedef Şahin (Indian Journal of Dermatology)
Prurigo pigmentosa (PP) is characterized by an initially pruritic inflammatory rash on the torso and nape of the neck, which fades subsequently to leave a reticular macular hyperpigmentation. Among the list of suggested potential aetiological factors, ketosis remains an indisputable cause. However, the mechanism(s) linking ketosis and PP remain largely unknown. Recently, dermatologists have been confronted with an outbreak of PP induced by ketogenic diets (KD) and bariatric surgeries. Atypical forms (bullous variant) and localizations have been encountered. Herein, we review the relevant literature on PP, discuss its link to ketosis with current and future perspectives and propose a hypothesis for its aetiopathogenesis.